Optimalisasi Kemandirian Kader dalam Penurunan Scabies melalui PHBS di Rumah Tahanan Kelas IIB Bangli - Candrawati, Sang Ayu Ketut; Citrawati, Ni Ketut; Andini, Ni Komang Sukra; Subhaktiyasa, Putu Gede (Universitas Baiturrahim, 2024)
The complex challenges in improving the health and welfare of prisoners at the Bangli Class IIB Detention Center demand a concrete response. Government Regulation No. 32/1999 affirms the right of every prisoner to obtain proper health services. One of the health problems that arise due to the crowded room occupancy is skin diseases, such as Scabies. To overcome the transmission of the disease, the first step that needs to be taken is the formation of Health Cadres. This Health Cadre Development activity aims to improve the health of WBP through counseling and training. This PKMS activity aims to improve the health of correctional prisoners (WBP) through the development of health cadres. The method used is Community-Based Interactive Approach (CBIA), WBP is actively involved in counseling and training related to clean and healthy living behavior (PHBS) and handling of Scabies skin disease in detention centers. The results of the activity showed an increase in knowledge and positive attitudes related to PHBS and the role of health cadres among prisoners. In conclusion, the formation of inmate health cadres can be a potential solution in efforts to prevent and manage diseases and improve the quality of life in detention centers